FUNGSI CONTROLLING MANAJEMEN PENDIDIKAN ISLAM DALAM PERSPEKTIF AL-QUR’AN - Arianto, Erwin (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
Controlling is an important component of management. Because of the inability to perform one of these management functions, many educational institutions are unable to prosper or are becoming more and more backward. This study is intended to answer questions: (1) How does control function in the perspective of Q.S. Al-Infitar/82: 10-12? (2) How is the function of control in the perspective of Q.S. Al-Fajr/89: 16? and (3) How does control function in the perspective of Q.S. Al-Naml/27: 40? The purpose of this study is to know and understand the management control function of Islamic education in the perspective of the Koran. The approach used is qualitative with the method of literature study. The sources used are secondary sources, namely library books. This study shows that: (1) The Function of Control in the Perspective of Q.S. Al- Infitar/82: 10-12 regarding the definition of control and supervision of education and its instruments; (2) Control Function in Q.S Perspective Al-Fajr/89: 16 regarding the principles and techniques of educational supervision and the ethical behavior of supervisors; and (3) Control Function in Q.S Perspective Al-Naml/27: 40 regarding the purpose and impact of educational supervision and the competence of supervisors